IDEAL MODEL OF ENVIRONMENTAL APPROVAL AS AN INSTRUMENT FOR POLLUTION AND ENVIRONMENTAL DAMAGE CONTROL IN SUSTAINABLE DEVELOPMENT - Elizabeth Ayu Puspita Adi; Airlangga Surya Nagara (Faculty of Law, Universitas Pekalongan, 2023)
This study is centered on the change in the arrangement of environmental permits as regulated in Law of the Republic of Indonesia Number 32/2009 concerning Environmental Protection and Management (UUPPLH) to environmental approval as regulated in Law of the Republic of Indonesia Number 11/2020 concerning Job Creation (Omnibus Law). This study aims to examine and analyze the implications of changes in environmental approval arrangements as regulated in the Omnibus Law concerning environmental licensing in the Environmental Protection and Management Law. A normative legal research method was employed in this study. The approaches used in this study included the statute approach and the conceptual approach. The results of this study confirmed the need to balance economic interests with environmental sustainability so that sustainable development can be well actualized.